Circuit analysis : theory and practice - Cunningham, David R.; Stuller, John A. (Boston : Houghton Mifflin, 1995)
This book is about: Fundamentals; Time-Domain circuit analysis; Frequency-domain analysis; Series and transform methods; Selected topics; ...
Keywords: Electric circuit analysis; Electric circuit analysis